Reserves and extraction of rare earth metals and elements as a key factor in the renewable energy sector development at the the world economy transformation current stage - R. D. Mingaleeva (Вестник университета)
The use of renewable energy sources, which are experiencing a period of rapid development, is one of the stages of the current energy transition, as the world community tries to ensure a future with zero CO2 emissions and to achieve energy independence and security. At the same time, for output of the wide range of products for the renewable energy sector, as well as for the development of energy depot systems, it is necessary to use rare earth elements and metals in production. The results of the analysis of data on reserves, production and calculated values of the resource availability coefficient of rare earth elements and metals shows that at the existing level of production, the proven reserves of cobalt will last for ≈ 50 years, lithium– for ≈ 200 years and rare earth elements – for ≈ 450 years, respectively, which leads to a limitation of the global transition speed to renewable energy sources and makes it necessary to look for new technical solutions.